PROSES PEMBELAJARAN PENJASORKES SECARA ONLINE PADA MASA PANDEMI COVID-19 - Isak Riwu Rohi (Nusa Cendana University, 2022)
The aims online teaching physical education online process pandemi covid-19 qualitative research methods to describe physical education learning activities were caried out online every day through the google class room and whatsap goup platforms to send material and assignment and evaluate student learning outcome, but experienced obstacles for teachers and student such as internet network disruptions, internet quota out and students do not have android handphone learning process online the pandemi covid-19 is the teacher ability to design and compile material, learning methods and aplications that are in accord with creativity of the teachers to motivate student to stay enthusiastic online learning and not become a psycological burden and depend on the disciplin of all parties to create schemes by compiling online system making flexible and simple.